2021
DOI: 10.1029/2020jb021208
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Moment Accumulation Response to Lateral Crustal Variations of the San Andreas Fault System

Abstract: Rheologic variations in the Earth's crust (like elastic plate thickness [EPT] or crustal rigidity) modulate the rate at which seismic moment accumulates for potentially hazardous faults of the San Andreas Fault System (SAFS). To quantify rates of seismic moment accumulation, Global Navigation Satellite Systems, and Interferometric Synthetic Aperture Radar data were used to constrain surface deformation rates of a four‐dimensional viscoelastic deformation model that incorporates rheological variations spanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(51 citation statements)
references
References 64 publications
(152 reference statements)
4
47
0
Order By: Relevance
“…We chose to compare a mid‐field and far‐field station because both have observations before and after the EMC event, which we consider until 1 January 2019 (roughly 9 years after the rupture), while most near‐field station observations started after the EMC event and had lower resolution. Using a previously published heterogeneous elastic plate rheology model for the Salton Trough (Ward et al., 2021), we first explored three time‐averaged viscosities (1e18, 3e18, and 1e19 Pa·s) (i.e., Dickinson‐Lovell et al., 2018; Hines & Hetland, 2016; Rollins et al., 2015; Spinler et al., 2015; Tang et al., 2020) for postseismic displacement of the EMC event (Figure 7). In the mid‐field, we found that up to 67% of the cumulative vertical displacements and 24% of the cumulative horizontal displacements could be explained by our modeled viscoelastic relaxation when a viscosity of approximately 1e18 Pa·s is adopted.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We chose to compare a mid‐field and far‐field station because both have observations before and after the EMC event, which we consider until 1 January 2019 (roughly 9 years after the rupture), while most near‐field station observations started after the EMC event and had lower resolution. Using a previously published heterogeneous elastic plate rheology model for the Salton Trough (Ward et al., 2021), we first explored three time‐averaged viscosities (1e18, 3e18, and 1e19 Pa·s) (i.e., Dickinson‐Lovell et al., 2018; Hines & Hetland, 2016; Rollins et al., 2015; Spinler et al., 2015; Tang et al., 2020) for postseismic displacement of the EMC event (Figure 7). In the mid‐field, we found that up to 67% of the cumulative vertical displacements and 24% of the cumulative horizontal displacements could be explained by our modeled viscoelastic relaxation when a viscosity of approximately 1e18 Pa·s is adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Including the restoring force of gravity is essential; our calculations show that it reduces the far‐field postseismic vertical amplitude by up to 25%, with only very minor effects on the horizontal components (Smith & Sandwell, 2004). A laterally varying elastic plate rheology was also included in the model (Ward et al., 2021), based on surface heat flow and depth of the lithosphere asthenosphere boundary, where the resulting average crustal rigidity is 33 GPa. This region has an average plate thickness of 66 km, which defines the average transition depth between the elastic layer and underlying viscoelastic half‐space.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations